Deletion of the 60-loop provides new insights into the substrate and inhibitor specificity of thrombin - Rezaie, Alireza R.; Yang, Likui (Thrombosis and Haemostasis, 2005)
Structural data have indicated that the 60-loop of thrombin with 8–9 insertion residues is responsible for the restricted substrate and inhibitor specificity of thrombin. However, previous deletion of 3–4 residues of this loop (des-PPW and des-YPPW) did not widen the specificity of thrombin, but further restricted it. The partial deletion of this loop also dramatically impaired the reactivity of thrombin with antithrombin (AT), protein C and fibrinogen, implicating a role for the productive interaction of the 60-loop with the target macromolecules. To further investigate the role of this loop, a mutant of thrombin was expressed in mammalian cells in which all 8 residues (Tyr-Pro-Pro-Trp-Asp-Lys-Asn-Phe) of the 60-loop were deleted (des-60-loop). In contrast to the partially deleted loop mutants, it was discovered that the des-60-loop mutant cleaved small synthetic substrates, clotted purified fibrinogen, and activated protein C with a near normal catalytic efficiency; however, its activity toward cofactors V and VIII was impaired ~2–4-fold. Direct binding and AT inhibition studies in the presence of heparin revealed that the affinity of heparin for interaction with exosite-2 of des-60-loop thrombin was impaired, though the reactivity of the mutant with AT and other plasma serpins was not impaired, but rather improved ~2-fold. These results suggest that the 60-loop plays a key role in regulating the specificity of thrombin by shielding the active-site pocket, but its productive interaction with the target molecules may not be as critical as has been speculated in previous reports.
Keywords: Thrombin; specificity; protein C; fibrinogen; antithrombin